2017
DOI: 10.1002/dta.2330
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of new psychoactive substances in oral fluids by means of microextraction by packed sorbent followed by ultra‐high‐performance liquid chromatography–tandem mass spectrometry

Abstract: In recent years, new drugs, commonly known as new psychoactive substances (NPS), appeared on the market, which include, among others, synthetic cannabinoids, cathinones, and tryptamine analogs of psilocin. The aim of this work was to develop and validate a new method for simultaneous screening and quantification of 31 NPS in oral fluid by ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). The chosen target analytes represented different chemical and toxicological NPS classes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…There are general problems with the reliability of NPS survey data, given the number of substances on the market, recollection of rather technical terms, or lack of information about the substance. Further validation of self‐reported NPS use could include the testing of biological samples but would be limited by the analytical capacity to detect NPSs that are new on the market or the fact that NPSs have been increasingly found in illegal drug samples .…”
Section: Discussionmentioning
confidence: 99%
“…There are general problems with the reliability of NPS survey data, given the number of substances on the market, recollection of rather technical terms, or lack of information about the substance. Further validation of self‐reported NPS use could include the testing of biological samples but would be limited by the analytical capacity to detect NPSs that are new on the market or the fact that NPSs have been increasingly found in illegal drug samples .…”
Section: Discussionmentioning
confidence: 99%
“…They developed MEPS with ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS). Linearity ranged over 3 or 4 orders of magnitude; precision and accuracy tests gave RSD values <25%, and accuracy ranged from 85.9 to 107% (Rocchi et al, 2018).…”
Section: Salivamentioning
confidence: 99%
“…The use of saliva samples in a study of 31 new psychoactive substances was reported by Rocchi et al (2018). They developed MEPS with ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS).…”
Section: Salivamentioning
confidence: 99%
“…These substances have become a global phenomenon, with more than 120 countries and territories having reported at least one NPS (UNODC Early Warning Advisory on New Psychoactive Substances, 2020). In particular, until recently, 950 substances have been reported to the (UNODC) by governments, laboratories, and partner organizations (Rocchi et al, 2018; United Nations Office on Drugs Crime, 2019, 2020). Although synthetic cannabinoids are rapidly evolving and there are serious difficulties controlling them on the market (Coulter et al, 2011), in Europe, the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA), through the EU Early Warning System, constantly monitors the use of synthetic cannabinoids.…”
Section: Introductionmentioning
confidence: 99%